Spirituality and the development of positive character among Filipino adolescents - Mansukhani, Roseann; Resurreccion, Roseann (Philippine journal of psychology)
"This study delved into the views, perceptions, and experiences of spirituality of Filipino adolescents to describe their conceptions of spirituality and spiritual development. Results revealed that Filipino adolescents define spirituality in terms of faith, personal relationship with God, and positive character, and describe spiritual persons as having faith in God, morality, positive personal qualities, a positive sense of self, spiritual connectedness, transcendent and relational sources of happiness, an ability to solve problems, and a sense of well-being."